Heartbreak Hotel - Kellerman, Jonathan (Kellerman, Jonathan. Alex Delaware novels., 2017)
"Alex Delaware and Milo Sturgis investigate the death of Alex's most mysterious patient to date in the sensational new thriller from the master of suspense, #1 New York Times bestselling author Jonathan Kellerman. At nearly one hundred years old, Thalia Mars is a far cry from the patients that child psychologist Alex Delaware normally treats. But the charming, witty woman convinces Alex to meet with her in a suite at the Aventura, a luxury hotel with a checkered history. What Thalia wants from Alex are answers to unsettling questions--about guilt, patterns of criminal behavior, victim selection. When Alex asks the reason for her morbid fascination, Thalia promises to tell all during their next session. But when he shows up the following morning, he is met with silence: Thalia is dead in her room. When questions arise about how Thalia perished, Alex and homicide detective Milo Sturgis must peel back the layers of a fascinating but elusive woman's life and embark on one of the most baffling investigations either of them has ever experienced. For Thalia Mars is a victim like no other, an enigma who harbored nearly a century of secrets and whose life and death draw those around her into a vortex of violence. Heartbreak Hotel is classic Delaware and classic Kellerman. Praise for Jonathan Kellerman "Jonathan Kellerman's psychology skills and dark imagination are a potent literary mix."--Los Angeles Times "Kellerman doesn't just write psychological thrillers--he owns the genre."--Detroit Free Press "A master of the psychological thriller."--People"--